Prevalence of sleep problems and its associated factors among the elderly living at the Jaffna divisional secretariat division - Jafran, M.M.; Ikram, S.M.; Sathees, S.; Sooriyakanthan, M. (Faculty of Allied Health Sciences, University of Jaffna, Sri Lanka, 2023)
Introduction: Sleep problems are more common among elderly due to physiological changes and poorly recognized due to negligence. Study on sleep problems and its associated factors to reduce sleep complaints and increase sleep quality among elders. Objective: To assess the prevalence of sleep problems and its associated factors among elderly living at the Jaffna divisional secretariat division. Methodology: The community based cross sectional study was conducted among 395 elderlies during November 2021 to November 2022. Participants were selected by two stage stratified random sampling. Predesigned interviewer administered questionnaire was used to gather the data. Data was analyzed in SPSS 25.0. Chi squared test was used to identify the association between the sleep problems and the selected factors. Results: Most of the participants (64.3%) were between 60-69 years of age. 55.7% of them were males, and 74.7% were married and (87.3%) were retired from previous employment. All the participant reported at least one sleep problem. Difficulty to fall sleep was the leading problem (74.6%) in this study, insufficiency of sleep duration (72.2%), dissatisfaction of sleep (71.4%), wake up earlier than they desired (68.3%) and night awakening (60.5%) were other identified major sleep problems. In addition, sleepiness (25.6%), not feeling well (17.3%) and disturbed body function (13.7%) during the day time were reported. Following factors were shown statistically significant association between sleep problems of study participants; age, gender, level of education, working status, permanent income, noise disturbance, light disturbance, temperature of the environment, day nap, incontinence, chronic worries, using addictive substances, family respect, using alcohol, sleep soon after dinner, watching TV before sleep, drinking caffeinated drinks before bed, smoking, reading in bed, chronic illness and difficulty in daily activities. Conclusion: Prevalence of sleep problems among the participants are high. Interventions to eliminate the sleep problems among the elderly are mandatory. The associated factors which are identified should be considered while planning such interventions.
Keywords: Prevalence; Sleep problems; Elderly; Disturbance